Corpus Linguistics based error analysis of first year Universiti Teknologi Malaysia students’ writing - Shamsudin, Sarimah; Mahady, Nurul Ros Adira (2010)
The ability to write in English among Malaysian university students is generally not at the most satisfactory level although English is considered as a second language. There has been a growing research interest in the analysis of errors students make in their English writing. The purpose of this study is to identify the errors made by first year UTM students in their writing. Besides that, this study also seeks to find out how much students know about the errors that they produce in writing besides investigating how they react towards these errors. For this study, 66 questionnaires were distributed to first year UTM students from the Faculty of Mechanical Engineering and the Faculty of Civil Engineering. Besides that, students’ samples of paragraph were also used to collect the intended data. Findings from the study show that from the 66 paragraph samples analyzed, a total of 1202 errors were found and then tagged according to the types of error. Besides that, findings from the questionnaire show that many of the students are not sure about their English proficiency level and most of them agreed that they would like to improve their English writing by addressing the errors that they make. The paper concludes with the overall summary of the study, limitations of the study as well as the pedagogical implications of the study.